Методологічний ізоморфізм як стиль наукового мислення Івана Франка - Сінченко, О.Д. (Слово і Час, 2019)
У статті реконструйовано методологічне мислення І. Франка на основі його різногалузевих
праць із метою синхронізації критеріїв, процедур і принципів доведення й виведення наукового
знання. Насамперед ідеться про побудову ізоморфних моделей мислення й методологічних
настанов, ґрунтованих на певних сталих світогляду й світорозуміння Франка як науковця кінця
ХІХ – початку ХХ століть.
Загалом стиль наукового мислення І. Франка тяжіє до індуктивізму. Докладний опис і
дослідження емпіричного матеріалу з використанням точних статистичних методів, аналогія
й порівняння – застосування наукових мов різного типу й системи понять, часто запозичених
із суміжних наук, зокрема загальнометодологічних (еволюція), постановка спільнонаукових
проблем, пошук і концептуалізація місць переходів галузевих методів і їхня апробація – усе це
й визначає стиль наукового мислення І. Франка. The present paper tries to reconstruct Ivan Franko’s methodological thinking on the basis of his
works and aims at synchronizing criteria, procedures and principles of proving and producing scholarly
knowledge. The main purpose here is building isomorphic models of thinking and methodological
instruction based on some Franko’s constants of the world view and understanding reality.
Franko as a scholar was interested in various fields: literary studies, ethnography, linguistics,
philosophy, social economics, law, political science, history, statistics etc. He intended to create
the ground for institutionalization of research work in Ukrainian society. His scholarly universalism
allowed using the knowledge from different fields simultaneously in order to study the same subject
from different perspectives. This subject was a society which he understood as the people, class,
and individual in his activities.
At every stage of his methodological refl ection, Franko adhered to clear determinism both in defining
the subject field of research and in constructing his assertions. But the attempt to single out the subject
knowledge in its pure form was complicated by the fact that he didn’t think of it separately from the
sphere of application, and therefore he was focused on the methods related to the practical use and
giving the opportunity of transferring the gained knowledge into the sphere of education.
In the definitions of scholarly work he used such characteristics as “thoroughness and precision”,
“good care and logic of scholarly analysis”, facts, observations, descriptions, comparisons, criticism,
analysis (more simple and versatile). These markers form a framework that makes it possible to
reconstruct the style of his thinking as a methodologist.
In general, Franko’s style of scholarly thinking tended to inductivism. This style was determined
by detailed description and study of empirical material with accurate statistical method; analogy
and comparison through applying different kinds of scholarly languages; conceptual systems, often
borrowed from the related spheres of knowledge, in particular notions of general methodology
(evolution); interest in general research problems; search for transitional joints of sectorial methods,
their conceptualization and approbation.